FAKTOR-FAKTOR YANG MEMPENGARUHI SISWA PUTUS SEKOLAH DI PROVINSI SUMATERA BARAT - Rita Diana RD (Balitbang Kemendikbud, 2021)
One of the targets aimed by the Smart Indonesia Program through the implementation of the 12-year Compulsory Education in the National Mid-Term Development Plan (RPJMN) 2015-2019 is to increase the education continuation rate which is marked by an increase in the average years of schooling and a decrease in the dropout rate. The dropout rate reflects school-age children who are no longer in school or who have not completed a certain level of education. The purpose of this study is to identify the factors that influence students dropping out of school. The data used is from the 2019 national socio-economic survey of West Sumatra Province, and the analysis method uses survival analysis with the Cox regression approach. The results show that the factors of residence, working/not working, receiving Rastra social assistance, taking care of the household, ever/never been married, status in the household, and the head of the household’s job affect the failure of a student to stay in school in West Sumatra Province in 2019. In addition, residents aged 15 years and above who live in rural areas, work, do not receive Rastra social assistance, take care of the household, have been married, are not in the nuclear family, having a household head who works in the agricultural sector have a significant decrease in the education survival rate at high school level.